Materials and process selection for engineering design - Farag, Mahmoud M., 1937- (Boca Raton, FL : CRC Press, 2014)
'Introducing a new engineering product or changing an existing model involves making designs, reaching economic decisions, selecting materials, choosing manufacturing processes, and assessing its environmental impact. These activities are interdependent and should not be performed in isolation from each other. This is because the materials and processes used in making the product can have a large influence on its design, cost, and performance in service. Since the publication of the second edition of this book, changes have occurred in the fields of materials and manufacturing. Industries now place more emphasis on manufacturing products and goods locally, rather than outsourcing. Nanostructured and smart materials appear more frequently in products, composites are used in designing essential parts of civilian airliners, and biodegradable materials are increasingly used instead of traditional plastics. More emphasis is now placed on how products affect the environment, and society is willing to accept more expensive but eco-friendly goods. In addition, there has been a change in the emphasis and the way the subjects of materials and manufacturing are taught within a variety of curricula and courses in higher education.This third edition of the bestselling Materials and Process Selection for Engineering Design has been comprehensively revised and reorganized to reflect these changes. In addition, the presentation has been enhanced and the book includes more real-world case studies.'--
Includes bibliographical references and index.
Keywords: Engineering design; Materials; Manufacturing processes